Acoustic emission during nonhomogeneous tensile deformation of ARMCO-iron - PAWEŁEK, A.; PILECKI, S. (Archives of Acoustics, 1993)
Measurements of acoustic emission count rates and RMS value in the ARMCO-iron have been carried out in tensile loading. Specimens of the ARMCO-iron have been used in two stands: annealed or pre-rolled and cut in parallel or perpendicular direction. Experimental results have been discussed in the light of possibility of dislocation proliferation and annihilation as well as their accelerated and decelerated movement.